PELATIHAN PENGENDALIAN PENYAKIT LAYU PADA TANAMAN JAHE DI DESA TARO KABUPATEN GIANYAR - Wijaya, I N.; Adiartayasa, W.; Sritamin, M.; Bagus, I G. Ngurah (Buletin Udayana Mengabdi, 2013)
Training on ginger wilt diseases was held at Taro village, Gianyar regency on 18 st July 2013. The activities aimed how to know control of ginger wilt diseases. The training was attended by 25 participants from local farmer groups of Taro village. The methods used in activities were lectures, demonstration and practice in the ginger field. All participants participated enthusiastically and hope they have the next intensive training again.